2021
DOI: 10.3389/fpls.2021.743680
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptomic and Bioinformatics Analyses Reveal the Molecular Mechanisms for the Differences in Seed Oil and Starch Content Between Glycine max and Cicer arietinum

Abstract: The seed oil and starch content of soybean are significantly different from that of chickpea. However, there are limited studies on its molecular mechanisms. To address this issue, we conducted integrated transcriptomic and bioinformatics analyses for species-specific genes and acyl-lipid-, starch-, and carbon metabolism-related genes. Among seven expressional patterns of soybean-specific genes, four were highly expressed at the middle- and late oil accumulation stages; these genes significantly enriched fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 92 publications
1
7
0
Order By: Relevance
“…Similar results were also found in low-starch and high-starch pea in Liu et al [67]. Third, we observed that starch synthesis-related genes in chickpea are highly expressed in the later stages of seed development, which is consistent with the main stages (mid-to-late stages) of nutrient accumulation in Steven et al [35], Garg et al [34], and Cheng et al [28]. This is more favorable for seed starch synthesis in chickpea.…”
Section: Dpe and Phs Interaction In Chickpea May Increase Higher Seed...supporting
confidence: 89%
See 3 more Smart Citations
“…Similar results were also found in low-starch and high-starch pea in Liu et al [67]. Third, we observed that starch synthesis-related genes in chickpea are highly expressed in the later stages of seed development, which is consistent with the main stages (mid-to-late stages) of nutrient accumulation in Steven et al [35], Garg et al [34], and Cheng et al [28]. This is more favorable for seed starch synthesis in chickpea.…”
Section: Dpe and Phs Interaction In Chickpea May Increase Higher Seed...supporting
confidence: 89%
“…Fourth, Scheidig et al [68] and Zeeman et al [69] showed that BMY activity is positively correlated with the extent of starch degradation, while Andriotis et al [70] found that reduced starch degradation rates in bmy mutants led to increased seed starch content in Arabidopsis. Finally, Cheng et al [28] found that high expression levels of starch synthesis-related genes APS (Ca_07632), APL (Ca_04774), GBSS (Ca_22418), and SSII (Ca_10512) in chickpea during the rapid synthesis stages of storage materials, and high expression levels of starch degradation-related gene BAM during the soybean seed development stages, resulted in higher seed starch content in chickpea compared to soybean. This is consistent with our findings in this study.…”
Section: The Regulatory Network Of Sucrose and Starch Metabolism-rela...mentioning
confidence: 99%
See 2 more Smart Citations
“…The expression patterns of genes in flower, leaf, stem, root, pod, and seed in soybean, cowpea, and kidney bean were analyzed via standardized expression levels, log 2 ( y + 1), where y was real expression level. Relative expression levels were defined as the ratio of the expression level of one gene to average expression level of all the genes in the species (deleting the genes with expression level less than 1.0) ( Zhang et al, 2018 ; Zhou et al, 2019 ; Cheng et al, 2021 ) and used to compare the differences of expression levels of genes in the flowers of soybean and cowpea. The TBtools and SigmaPlot software packages were used to draw HeatMap and relative expression levels, respectively.…”
Section: Methodsmentioning
confidence: 99%